Le riviste pedagogiche dall'analogico al digitale: il caso di "Studi sulla formazione" - Cosimo Di Bari (Firenze University Press, 2019)
The digital revolution implied significant consequences for the pedagogical journals: the transition from analogue to digital has favored an exponential increase of their  spread and their circulation. The contemporary era is increasingly characterized by the proliferation of knowledge sources, but the subject has more difficulty in finding an orientation between reliable resource: the pedagogical journal "Studi sulla Formazione" plays an important role in promoting critical thinking and scientific rigor in educational professionals.